Double-Deficit Hypothesis in a Clinical Sample: Extension Beyond Reading. (September 2016) - Heikkilä, Riikka; Torppa, Minna; Aro, Mikko; Närhi, Vesa; Ahonen, Timo
This study explored the double-deficit hypothesis (DDH) in a transparent orthography (Finnish) and extended the view from reading disabilities to comorbidity of learning-related problems in math and attention. Children referred for evaluation of learning disabilities in second through sixth grade ( N = 205) were divided into four groups based on rapid automatized naming (RAN) and phonological awareness (PA) according to the DDH: the double-deficit group, the naming speed deficit–only group, the phonological deficit–only group, and the no-deficit group. The results supported the DDH in that the prevalence and severity of reading disability were greatest in the double-deficit group. Despite the greater prevalence of reading disabilities in single-deficit groups compared to the no-deficit group, the means of reading measures in the single-deficit groups were similar to those of the no-deficit group. The PA single-deficit group was poorer in spelling than the no-deficit group and single-naming-deficit group. Deficits in RAN or PA were primarily linked to reading disabilities but not with math or attention problems. The results supported the DDH partially and indicate that deficits in RAN and PA are specific to reading disabilities.